Evaluation of Antioxidant Activity of 1, 2, 4-Triazole Derivatives With Morpholine Moiety - Shcherbyna, R. O.; Pryhlo, E. S.; Duchenko, M.; Kulagina, M.; Kudria, V.; Vashchuk, V.; Щербина, Роман Олександрович; Пругло, Євген Сергійович (My University, 2022)
The aim of the work was to study the antioxidant activity of 4-R- 3-(morpholinomethyl)-4H-1,2,4-triazole-5-thioles and their alkyl derivatives in vitro using the method of non-enzymatic initiation of lipid peroxidation. Among the 45 compounds studied, 8 showed varying degrees of AOA. The most pronounced AOA has 4-amino-3-(morpholinomethyl)-4H-1,2,4-triazole-5-thiol. It was found that in most cases the introduction in alkyl-derivatives of 4-R- 3-(morpholinomethyl)-4H-1,2,4-triazole-5-thioles free amino group or phenyl substituent to the N4 atom of the 1,2,4-triazole nucleus, accompanied with increasing of AOA for test substances. In almost all cases, the presence on the N4 atom of 1,2,4-triazole nucleus methyl or ethyl groups has the opposite effect, even in comparison with control groups.
Shcherbyna R. O. - ORCID: 0000-0002-9742-0284; Pryhlo E. S. - ORCID: 0000-0002-4705-7261.
Keywords: 1,2,4-triazole; antioxidant activity; in vitro method